Platelet-Derived Growth Factor-D Activates Complement System to Propagate Macrophage Polarization and Neovascularization - Xiong, Zhen; Wang, Qianqian; Li, Wanhong; Huang, Lijuan; Zhang, Jianing; Zhu, Juanhua; Xie, Bingbing; Wang, Shasha; Kuang, Haiqing; Lin, Xianchai; Lee, Chunsik; Kumar, Anil; et al. (Frontiers in Cell and Developmental Biology, 2021)
Platelet-derived growth factor-D (PDGF-D) is highly expressed in immune cells. However, the potential role of PDGF-D in the immune system remains thus far unclear. Here, we reveal a novel function of PDGF-D in activating both classical and alternative complement pathways, which in turn markedly increased chemokine and cytokine responses to promote macrophage polarization. Pharmacological targeting of the complement C3a receptor using SB290157 alleviated PDGF-D-induced neuroinflammation by blocking macrophage polarization and inhibited pathological choroidal neovascularization. Our study thus suggests that therapeutic strategies targeting both PDGF-D and the complement system may open up new possibilities for the treatment of neovascular diseases.